PENERAPAN METODE TANYA JAWAB DAN DEMONSTRASI DALAM PEMBELAJARAN FIQIH MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS III PADA MI ISLAMIYAH SUROWONO KABUPATEN KEDIRI - Sri Putrianingsih; Ziara Sufi Rahmawati (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The role of the teacher in learning activities is very important to moivate students, of course regardless of themethods applied. The research “the application of the question and answer and demonstration method in figh learning to increase students’ learning motivation in class III at Mi Islamiyah Surowono, Kediri regency. The problemis whether the question and answer and demonstration method in figh learning can be carried out in 3(three) cycles qualitatively using observation, interview and documentation methods. From cycles 1to 3 it show that applying the question and answermethod can increase student motivation, especiallyin learning figh. This action is inlearning previously, students did not show creativity , instead they were boring. Keywords : question and answer method, demontration method, figh learning